Kindler's Syndrome with Recurrent Neutropenia: Report of Two Cases from Saudi Arabia - Binamer, Yousef; Chisti, Muzamil A. (Journal of Pediatric Genetics, 2020)
Kindler syndrome (KS) is a rare photosensitivity disorder with autosomal recessive mode of inheritance. It is characterized by acral blistering in infancy and childhood, progressive poikiloderma, skin atrophy, abnormal photosensitivity, and gingival fragility. Besides these major features, many minor presentations have also been reported in the literature. We are reporting two cases with atypical features of the syndrome and a new feature of recurrent neutropenia. Whole exome sequencing analysis was done using next-generation sequencing which detected a homozygous loss-of-function (LOF) variant of FERMT1 in both patients. The variant is classified as a pathogenic variant as per the American College of Medical Genetics and Genomics guidelines. Homozygous LOF variants of FERMT1 are a common mechanism of KS and as such confirm the diagnosis of KS in our patients even though the presentation was atypical.
Keywords: photosensitivity; genodermatosis; Kindler's syndrome; poikiloderma; epidermolysis bullosa